4D deformation based on double-layer structure of the pumpkin/paper. (January 2021) - Chen, Fengying; Zhang, Min; Liu, Zhenbin; Bhandari, Bhesh
Graphical abstract: Highlights: The deformation of the pumpkin/paper double-layer structure was studied. The effect of drying time, printing path and thickness on deformation was studied. The changes of moisture content, color and texture during the deformation process were studied. The directional deformation of the double-layer structure can prepare complex shapes. Abstract: In this work, the controlled deformation of the double layer structure of 3D printed pumpkin/paper was studied. Firstly, the rheological analysis was done to characterize the rheological properties of different solid-liquid ratio of pumpkin puree, and were related to the extrusion behavior and support performance during 3D printing. The double-layer structure of the pumpkin/paper had different temperature response characteristics due to the composition and starting moisture content, so there was an anisotropy in the thickness direction. The pumpkin puree having the moisture loss characteristic acted as a deformation driving layer to cause the structure to bend toward the pumpkin puree side. In addition, different deformation effects were obtained by controlling the drying time, printing path and thickness, thereby achieving directional deformation of the printed structure. The changes of moisture content, color and texture during the deformation of the double-layer structure of pumpkin weighing paper were measured and correlated with the deformation of the double-layer structure of pumpkin weighing paper.